Financial Development and Poverty Reduction : Can There Be a Benefit Without a Cost? - Guillaumont Jeanneney, Sylviane; Kpodar, Kangni (Washington, D.C. : International Monetary Fund, 2008)
This article investigates how financial development helps to reduce poverty directly through the McKinnon conduit effect and indirectly through economic growth. The results obtained with data for a sample of developing countries from 1966 through 2000 suggest that the poor benefit from the ability of the banking system to facilitate transactions and provide savings opportunities but to some extent fail to reap the benefit from greater availability of credit. Moreover, financial development is accompanied by financial instability, which is detrimental to the poor. Nevertheless, the benefits of financial development for the poor outweigh the cost.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet